Formulation and Characterization of Urea Slow-Release Fertilizer Based on Disposable Diaper Waste with Activated Carbon as Additives - Kusumaningrum, Maharani; Rengga, Wara Dyah Pita; Hibatullah, Ridwan Dani; Nanggala, Pragusti Lintang Adhi; Ichwan, Rizky; Nada, Athiya Rihadatul ‘Aisy Qothrun (Sainteknol : Jurnal Sains dan Teknologi, 2025)
Disposable diapers are non-biodegradable waste that can pollute the environment. Disposable diapers contain super absorbent polymer (SAP) which has an absorption capacity of up to 1,000 times. SAP can be combined with activated carbon as a coating agent in urea slow-release fertilizer (SRF) production. This research aims to analyze the effect of urea SRF formulation (FA, FB, FC, and FD), with the combination of SAP and activated carbon, on the characteristics and nitrogen release behavior. SRF was characterized by Scanning Electron Microscope (SEM), Fourier Transform Infra-Red (FTIR), and Water Retention (WR) testing to determine the morphological structure, functional groups, and the ability of the sample to retain water during observation. The percentage of nitrogen release from SRF was calculated using the Kjeldahl method. The results of SEM characterization show that the thickness of the layer formed is about 63.5 µm. Different sample formulations affect the intensity of the functional groups produced. From all formulations, FD showed the highest WR and the lowest nitrogen release percentage with values of 80.2% and 20.4%, respectively. In general, it can be concluded that the combination of SAP from disposable diapers and activated carbon can be used as a coating agent in SRF production.